ASEAN Centrality: Comparative Case Study of Indonesia Leadership - Ratih Indraswari (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2022)
For almost 60 years of establishment, ASEAN has received praises and disdain from institutional scholars. It is heralded as the only regionalism in Southeast Asia able to manage regional order through its normative power, but also criticized for the same power. ASEAN once again faces a challenge with the looming of Myanmar crisis. The research aimed to find out whether ASEAN Centrality, the primacy of ASEAN in addressing regional issues, is still strong enough amidst the crisis. The research provided an analysis on ASEAN Centrality by adopting an individual-state leadership concept portrayed by Indonesia as a de facto leader of ASEAN. The research methods employed qualitative explorative research by focusing on comparative case studies on the Preah Vihear and Myanmar cases. The research finds that in both cases, ASEAN Centrality prevails. However, its strength varies as Indonesia's leadership depends on mutually inclusive variables. These determining variables are institutional mandates, the domestic interest of followers, and external pressures.